Chitosan‐Stabilized PtAu Nanoparticles with Multienzyme‐Like Activity for Mixed Bacteria Infection Wound Healing and Insights into Its Antibacterial Mechanism - Wen, Yujuan; Chen, Wenxin; Wu, Ruimei; Guo, Jianpeng; Liu, Xin; Shi, Boling; Zhang, Cunshan; Wu, Lina; Zheng, Yanjie; Liu, Ailin; Lin, Liqing (Small structures, 2024)
Traditional antibacterial agents are often observed to be ineffective because bacteria evolved to strains with greater antibiotic resistance. Here, vigorous chitosan‐stabilized PtAu nanoparticles (CSPA) with multienzyme‐like activity are successfully fabricated, which serve an effective artificial nanozyme to enhance antibacterial activity for mixed bacterial infection wound treatment. Ultrasmall size CSPA exhibits excellent hydrophilicity and biocompatibility, possesses strong oxidase‐ and peroxidase‐like activity generating a substantial amount of ROS (O2−$$ O_{2}^{-}$$, 1O2, ·OH) to cause oxidative damage to bacteria, also demonstrates nicotinamide adenine dinucleotide dehydrogenase‐like activity disrupting the bacterial respiratory chains, and subsequently impedes adenosine triphosphate production. CSPA exhibits favorable broad‐spectrum antibacterial activity at very low concentrations, prevents bacterial resistance, and completely inhibits bacterial biofilm formation. Antibacterial Mechanism of CSPA by the transcriptomics is further revealed that CSPA can induce bacterial oxidative stress, hinder bacterial energy metabolism, and disrupt the synthesis and function of bacterial cell walls and cell membranes. In vivo, CSPA inhibits the mixed bacterial population at the wound site and promotes wound healing in rats. This study introduces a novel antibacterial approach, providing important insight into the antibacterial mechanism of CSPA nanozymes and promoting the advancement of nanocatalytic materials in biomedical applications. This work presents the preparation of ultrasmall chitosan‐stabilized PtAu (CSPA) nanoparticles with multienzyme‐like activity for antibacterial research. The CSPA exhibits good antibacterial, antidrug resistance, antibiofilm, and anti‐infective activities. Transcriptomics further reveal that CSPA primarily targets pathways associated with oxidative stress, energy metabolism, and cell wall and membrane synthesis to exert its antibacterial activity.